2022
DOI: 10.1177/10935266221096939
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Antral Mucosal Changes in Children With Intestinal Metaplasia

Abstract: Objectives: The gastric mucosal change accompanying gastric antral intestinal metaplasia (IM) in the pediatric population and its clinical implications remain unclear. Methods: We retrieved all patients younger than 18 years who had upper GI endoscopy with a pathology diagnosis of antral IM between 2009 and 2020. Each biopsy was evaluated for the presence of dysplasia, Helicobacter pylori, gastritis, and other pathologic changes. Results: A total of 134 patients with antral IM were identified; 72 (53.7%) with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 26 publications
0
4
0
1
Order By: Relevance
“…Consistent with our findings, a recent pediatric meta‐analysis and systematic review found a low GIM frequency of 1.2% in antral biopsies and 0.9% in corpus biopsies (27). Another recent study identified a 0.75% frequency of GIM in antral biopsies in children (19). We did not observe reactive gastropathy or GA in our GIM patients.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Consistent with our findings, a recent pediatric meta‐analysis and systematic review found a low GIM frequency of 1.2% in antral biopsies and 0.9% in corpus biopsies (27). Another recent study identified a 0.75% frequency of GIM in antral biopsies in children (19). We did not observe reactive gastropathy or GA in our GIM patients.…”
Section: Discussionmentioning
confidence: 95%
“…Similarly, most of the published pediatric series have found GIM in association with H pylori infection (17,30,35–37). A recent estimate of GIM frequency in H pylori ‐infected children was 2.5% and 1.5% in antral and corpus biopsies, respectively (19,20,27). The number of patients with evidence of H pylori in gastric biopsies in our series was low, making it difficult to draw conclusions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gastrik eozinofili sık patolojik bulgulardan iken bizim çalışmamızda sadece 1 hastada mevcuttu. Her iki çalışmada da displazi gözlenmedi(14). GIM ile displazi ve karsinom birlikteliği çocuklarda nadiren görülür, çünkü öncelikle bunların gelişmesi için gereken süre bireyi yetişkinliğe taşır(15).…”
unclassified